Efficiency of natural wood extractives as wood preservatives against termite attack - Syofuna, A.; Banana, A.Y.; Nakabonge, G. (Maderas. Ciencia y Tecnología, 2025)
Wood extractives play a major role in the protection of wood against termite and fungal attack. Wood extractives from three hard wood species of Milicia excelsa, Albizia coriaria and Markhamia lutea that are known to be very resistant against termite attack and fungal decay were studied to assess their role as wood preservatives in Uganda. Acetone, hexane and distilled water were used in the extraction of these compounds from the outer heartwood of the selected durable species. Extraction was done using a soxhlet extractor. The extractives obtained were used to treat Pinus caribaea and Antiaris toxicaria species known to be susceptible to termites and fungal attack. Treated blocks were then exposed to Macrotermes bellicosus termites in the fi eld. It was observed that wood extracts used as preservatives improved the resistance of less durable samples to termite attack by 50% compared to the controls. It was also observed that removal of extractives decreased resistance of the durable samples. It can be concluded that wood extractives contribute greatly to the protection of less durable wood species against termite attack.